Transitioning to sustainability: pathways, directions and opportunities. (1st January 2013) - Boyle, Carol; Head, Peter; Hood, David; Lawton, Maggie; Lowe, Ian; O'Connor, Martin; Peet, John; Schreier, Hans; Vanegas, Jorge
The transition to sustainability requires not only an understanding of the risks that society is facing but the development of pathways that will enable the shift towards sustainability. Such risks include not only resources and global warming but also established economic models and social ethics and values. This paper identifies how the risks facing global societies are being addressed, and outlines methods that are being used to identify and create dialogues with stakeholders. Cities, due to their direct role in ensuring that the needs of their communities are met, are providing leading visions and strategies in achieving sustainability in collaboration with other cities and with companies. Models for identifying stakeholders and enabling multiple perspectives to be integrated into discussions have been developed and are being put into practice. These are being enhanced through use of computer models, geographic information systems, mind mapping and matrix tools to develop visions and strategies for sustainable cities.